2018
DOI: 10.2106/jbjs.oa.18.00006
|View full text |Cite
|
Sign up to set email alerts
|

Essential Amino Acid Supplementation Mitigates Muscle Atrophy After Total Knee Arthroplasty

Abstract: Background:Substantial muscle atrophy occurs after total knee arthroplasty (TKA), resulting in decreased strength and impaired mobility. We sought to determine whether perioperative supplementation with essential amino acids (EAA) would attenuate muscle atrophy following TKA and whether the supplements were safe for ingestion in an older surgical population.Methods:We performed a double-blind, placebo-controlled, randomized trial of 39 adults (age range, 53 to 76 years) undergoing primary unilateral TKA who in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
63
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(72 citation statements)
references
References 29 publications
(36 reference statements)
7
63
1
Order By: Relevance
“…In the present study, whether the time of BCAA ingestion was at breakfast or post-exercise, there was no significant main effect or interaction with skeletal muscle mass. This result is in agreement with multiple previous studies [ 2 , 14 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Abe et al [ 25 ] reported that stroke patients had decreased skeletal muscle mass on both the affected and unaffected sides of the body starting one month after onset.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In the present study, whether the time of BCAA ingestion was at breakfast or post-exercise, there was no significant main effect or interaction with skeletal muscle mass. This result is in agreement with multiple previous studies [ 2 , 14 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Abe et al [ 25 ] reported that stroke patients had decreased skeletal muscle mass on both the affected and unaffected sides of the body starting one month after onset.…”
Section: Discussionsupporting
confidence: 94%
“…Recently, combined intervention has been viewed with keen interest; the effects of combined intervention on improving muscle strength or mass has gained a certain consensus [ 1 , 2 , 3 , 4 , 5 , 6 , 17 , 18 ], and the range of its use is expanding. Previous studies were done in patients with stroke [ 10 ], hip fracture [ 19 ], and artificial joint replacement [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…We then reviewed the titles and abstracts of 83 studies to assess their eligibility, of which 26 were considered relevant to this study and thus underwent full-text assessment ( Figure 1 ). The final sample comprised six RCTs [ 31 , 32 , 61 , 62 , 63 , 64 ] published between 2013 and 2019. All of the six RCTs were included in the qualitative synthesis, and five of them were included in the meta-analysis [ 31 , 32 , 61 , 62 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Skeletal muscular atrophy is an unsolved issue despite of the remarkable progression of modern medication. Although novel treatments, such as photobiomodulation therapy [ 30 ], electromyostimulation [ 34 ], and amino acid supplementation [ 35 , 36 ] with or without a combination of traditional rehabilitation, have been proposed to ease the aggravation of atrophy or even to increase the muscle mass, unfortunately the effectiveness of above mentioned therapies are still limited. On the other hand, Ganoderma sp., the traditional Chinese medicinal mushrooms, which were popularly used to improve pathological conditions, such as hepatic functional impairment and cancer therapy, have recently drawn attention due to their core component, “sacchachitin” that was clinically found to be capable of improving muscular atrophy.…”
Section: Discussionmentioning
confidence: 99%